Efforts to Improve Early Childhood Cognitive Abilities through Learning Videos in Islamic Education Learning at RA Nurussalam Kuningan - Mulyaningsih, Hety; Maulidah, Idah (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to determine the increase in cognitive development of group A children through learning video media at RA Nurussalam, Ragawacana Village, Kramatmulya District, Kuningan Regency. The type of research is collaborative classroom action research with the Kemmis & Mc Taggart model. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The subjects of the study were children in group B1 at RA NURUSSALAM, Ragawacana Village, Kramatmulya District, Kuningan Regency, totaling 8 people. The object of the study was children's cognitive abilities through learning video media. Data collection techniques used observation, documentation, and interviews. The instruments used in the observation were research sheets, for documentation using a photo camera to document all children's activities during the activity and interviews using interview guidelines with GROUP A teachers to find out the conditions and problems faced. In the Pre-Cycle, out of 8 students who showed Very Good Development (BSB), none, Developing According to Expectations (BSH) there was 1 child, namely 12.5%, Starting to Develop (MB) there were 7 children, namely 87.5% and Not Yet Developing (BB) there were 0 children, namely 0%. In cycle I, out of 8 students who showed Very Good Development (BSB), there were 2 children, namely 25.0%, Developing According to Expectations (BSH) there were 3 children, namely 37.5%, Starting to Develop (MB) there were 3 children, namely 37.5% and Not Yet Developing (BB) there were none. While in Cycle II there was a fairly good increase, out of 8 students who got Very Good Development (BSB), there were 5 children, namely 62.5%, Developing According to Expectations (BSH) there were 2 children, namely 25%, Starting to Develop (MB) there was 1 child, namely 12.5%, and Not Yet Developing (BB) there were none. And in cycle III, children's cognitive development developed very well, namely from 8 students, 7 children showed Very Good Development (BSB) which was 87.5%, Developing According to Expectations (BSH) there was 1 child, namely 12.5%, Starting to Develop (MB) none, and Not Yet Developing (BB) none.